Assessment of CO2 storage potential in high water-cut fractured volcanic gas reservoirs—Case study of China's SN gas field. (1st March 2023) - Wang, Chengwei; Wang, Wendong; Su, Yuliang; Zhao, Yang; Wen, Jiayi; Li, Lei; Hao, Yongmao
Highlights: In this study, combined with the salinity characteristics of the formation water of the target block, a buried-potential evaluation study on typical wells in volcanic gas reservoirs is conducted, the gas–water distribution characteristics of the gas reservoir after CO2 injection are evaluated, and the CO2 injection timing and volume are optimized. The simulation results show that the different ion content in the formation water leads to two reaction processes: dissolution and precipitation of reservoir minerals. When the CO2 in the formation water is low, the reservoir is dominated by dissolution reaction and the CO2 mineralization buried amount is negative; gradually decreasing with the age of the reservoir. As more CO2 is injected into the formation, a considerable amount of HCO3 – is produced. Combining the total amount of CO2 dissolution and mineralization storage, the total amount of storage is the highest, when the injection rate is 2.5 × 10 5 m 3 /d. indicating that SN volcanic gas reservoir has significant CO2 -storage potential. Abstract: CO2 storage is an important technique for achieving both carbon peak and carbon neutralization, and depleted gas reservoirs are primary potential candidates for geological CO2 storage. After 15 years of development, the recovery rate of the SN gas field in China has reached 70 % and entered the middle and late stages. Most importantly, it has entered the stage of high water cut, rendering the stabilization of production challenging. As the gas produced in this gas reservoir contains a considerable amount of CO2, high water-bearing wells can be selected for CO2 storage in volcanic depleted gas reservoirs on site. Therefore, in this study, combined with the salinity characteristics of the formation water of the target block, a buried-potential evaluation study on typical wells in volcanic gas reservoirs is conducted, the gas–water distribution characteristics of the gas reservoir after CO2 injection are evaluated, and the CO2 injection timing and volume are optimized. The results show that the different ion content in the formation water leads to two reaction processes: dissolution and precipitation of reservoir minerals. When the CO2 in the formation water is low, the reservoir is dominated by dissolution reaction and the CO2 mineralization buried amount is negative; gradually decreasing with the age of the reservoir. As more CO2 is injected into the formation, a considerable amount of HCO3 – is produced. In this context, the formation water is dominated by a precipitation reaction, and the CO2 mineralization buried amount is positive. In 2026, compared with the dissolved buried capacity of 1.0 × 10 5 m 3 /d, the injection rate of 2.5 × 10 5 m 3 /d will increase by 6.38 × 10 8 mol. When the injection rate is 1.5 × 10 5 m 3 /d, the mineralization buried capacity is the highest (2.02 × 10 5 mol.). Combining the total amount of CO2 dissolution and mineralization storage, the total amount of storage is the highest (1.38 × 10 8 mol.) when the injection rate is 2.5 × 10 5 m 3 /d, indicating that the SN volcanic gas reservoir has significant CO2 -storage potential. Guided by the research results of this study, typical wells have been selected to inject CO2 for storage purposes.